Cross polarization conversion metasurface for fixed wireless and ku‐band applications. (9th November 2021) - Abdullah,; Kamal, Babar; Ullah, Sadiq; Khan, Bilawal; Ali, Horia; Rahim, Tariq
Summary: A dual broadband cross‐polarization‐conversion (CPC) metasurface is designed, simulated, fabricated and results are experimentally verified. The designed patch of metasurface unit cell is composed of a triangular loop connected with two arcs at both ends. The metasurface is made of 44 × 44 unit cells arranged periodically on 1.6‐mm‐thick FR4 dielectric substrate, backed by a metallic copper sheet as a reflector surface on the back side of the dielectric substrate. The surface achieves CPC in two bands (7–8.5 GHz) and (13–19 GHz), in the microwave regime. The simulation results show that the polarization conversion ratio (PCR) is almost 90% for both x polarized (TM) and y polarized (TE) electromagnetic (EM) waves. The proposed metasurface is fabricated on 308 × 308 mm 2 FR4 substrate plane. The simulated results are validated and are found in close covenant with the measured results. Abstract : A cross polarization converting metasurface (PCMS) for fixed wireless and ku‐band applications is demonstrated. The proposed converter achieves cross polarization conversion in two bands (7–8.5 GHz) and (13–19 GHz) in the microwave region with a polarization conversion ratio of 90% in both bands. The PCMS can be used as polarization state rotator, gain and performance enhancer for antenna designing, and many other microwave appliances.